A rare myoepithelioma of the sinonasal cavity: case report - Sayed, Suhail I (BioMed Central, 2008)
Myoepithelioma is a rare benign neoplasm. Pure accounting for less than 1% of all salivary gland tumors. Only three cases of sinonasal myoepithelioma have been reported in the literature. Diagnosis of myoepithelioma through light microscopy is possible and immunohistochemistry is done to facilitate the diagnosis. The lesion is so rare that there are no specific indications/guidelines for its treatment. We report to you a rare case of sinonasal myoepithelioma in a 57 year old Asian female. Myoepitheliomas are rare tumours that account for only about 1% of all salivary gland tumors. Most are benign, but some can be malignant. Only three cases of sinonasal myoepithelioma have been reported in the literature so far.